Ultrastructural characteristics of mitochondria in rat cardiomyocytes in the early cardiogenesis. - Ivanchenko M.V.; Tverdokhlib I.V. (Морфологія, 2012)
We have studied ultrastructure of mitochondria in embryos rat’s myocardium at different stages of prenatal ontogenesis. It is shown that in the sarcoplasm of contractile cardiomyocytes determined significant polymorphism of mitochondria, ratio of all types of mitochondria is different of stages of rat’s ontogenesis and is significantly different from those of contractile cardiomyocytes of newborns. Established, that the distribution of different types of mitochondria is heterogeneous in specific subcellular localization, due to the functional features of these organelles. During prenatal development of rat heart is regular increase in the degree of heterogeneity of the mitochondrial apparatus. At the same time, the formation and the degree of development in different parts of the heart are not the same. The most active development rates of mitochondrion occur in the myocardium of the left and right ventricles, the lowest – in the atrial, at the early stages of cardiogenesis by the "low-energy" organelles, then, with a significant increase of the "high-energy" mitochondria.